PENERAPAN PROBLEM BASED LEARNING PADA MATERI POLA DASAR FASE E DI SMK NEGERI 1 JABON - Rizqi Amelia, Fariha; Mayasari, Peppy; Marniati; Yuniati, Mita (Jurnal Socia Akademika, 2025)
This study aimed to evaluate the effectiveness of the Problem Based Learning (PBL) model in improving students’ learning outcomes on the basic pattern elements (phase E) in fashion design subject at SMK Negeri 1 Jabon. The research employed a quasi-experimental design with a quantitative approach. The sample consisted of 33 students from one class selected purposively. Data were collected through observation sheets on PBL implementation, learning outcome tests (pretest and posttest), and student response questionnaires. Data were analyzed using descriptive statistics by comparing pretest and posttest scores and calculating the percentages of implementation and student responses. The results showed that the implementation of the PBL model was categorized as very good, with an average of 91% in the first session and 91.6% in the second. Students’ learning mastery improved significantly from 45% (pretest) to 91% (posttest), with a 46% increase. Student responses were also highly positive, with an average score of 88.2%. These findings indicate that the PBL model effectively enhances students’ engagement, content understanding, and critical thinking skills. The implication of this study suggests that the PBL model is suitable for practical learning in fashion design education that emphasizes contextual problem solving and collaborative learning